Influence of food behavior and physical activity in relation to the overall physical condition of Romanian students - Savu, Catalin Vasile; Gheorghiu, Aurelian; Trandafir, Marius; Serea, Cristian; Barna, Octavian (Progress in Nutrition, 2019)
The aim of the present study was to determine the influence between food behavior and physical activities in relation to the overall physical condition of Romanian students. The research study was conducted on a group of athletic and non-athletic students from one college and two faculties from Galati County, in Romania. For this purpose, a cross-sectional analysis of data was processed from a representative sample of 1,214 students aged between 19 and 25 years old who answered a self-reported diet history questionnaire (DHQIII) questionnaire to establish their food habits quantified in healthy eating index (HEI) 2015 score and self-administered international physical activity questionnaire (IPAQ) questionnaire to assess their physical activity. The EUROFIT test battery was used to determine the overall physical condition of the subjects. Within this study, after 3 weeks of the initiation of the main study, a different subgroup of 228 subjects aged 19 ± 25 years old also participated in an ancillary study including an interview about their physical activities and an interview with a dietician before completing IPAQ and DHQIII questionnaires. The objective was the determination of the overall physical condition of the subjects that have used EUROFIT tests battery. To express the students’ overall performance in one score, it was calculated a total test score. The percentage of athletic male students overall involved in intense sports activities was 26.72% which was higher with 3.8% than the percentage of athletic female students (22.92%) tested in the main study. Median values of combined activities were expressed in metabolic equivalent min/week and ranged from 394.12 to 5586.44 for male students and from 412.53 to 4318.81 for female students. For the food habits, the median values for the HEI) score ranged from 50.4 to 55.1 for male students and from 51.3 to 54.2 for female students surveyed in the main study. Body fat percentage median values ranged from 22.6 to 16.2 for male students and from 28.6 to 20.1 for female students and body mass index median values ranged from 23.64 to 21.02 for male students and from 22.14 to 20.19 for female students that participated in the main study. The multivariate analysis of the results showed a strong correlation between their food habits and their overall physical conditions. The Pearson correlation coefficient between the HEI and total Eurofit test score values had the value p = 0.046 < 0.05 for male students and p = 0.044 < 0.05 for female students tested in the main study. The statistical analysis showed that there are strong positive correlations between the indices calculated in the main study and those in the ancillary study. Students with a healthy diet and high physical activity have had a higher overall physical condition than sedentary students or those with less healthy eating habits.